2012
DOI: 10.3168/jds.2011-5206
|View full text |Cite
|
Sign up to set email alerts
|

Effects of abomasal infusion of tallow or camelina oil on responses to glucose and insulin in dairy cows during late pregnancy

Abstract: Late pregnancy is associated with moderate insulin resistance in ruminants. Reduced suppression of lipolysis by insulin facilitates mobilization of nonesterified fatty acids (NEFA) from adipose tissue, resulting in elevated plasma NEFA concentrations. Decrease in dry matter intake (DMI) before parturition leads to accelerated lipomobilization and increases plasma NEFA, which may further impair insulin sensitivity. The aim of the study was to evaluate the effects of elevation of plasma NEFA concentration by abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 60 publications
3
45
0
Order By: Relevance
“…As expected, cows with high BCS and BFT had also higher concentrations of circulating NEFA during the weeks preceding HEC tests, indicating precalving mobilization of body fat (Grummer, 1993;Kokkonen et al, 2005). High levels of circulating NEFA are known to negatively affect the effect of insulin at the level of the glucose and FA metabolism, as demonstrated experimentally in dairy cows by intravenous infusion of tallow emulsion (Pires et al, 2007;Salin et al, 2012) and by prolonged fasting (Oikawa and Oetzel, 2006), whereas in early lactation NEFA level is negatively associated with glucose decrease after insulin injection (Kerestes et al, 2009). Similarly, in the present research, impaired insulin action at the level of the glucose metabolism (EC50 glucose and max glucose ) and the FA metabolism (min NEFA ) was associated with high levels of NEFA in the weeks preceding the HEC test.…”
mentioning
confidence: 57%
“…As expected, cows with high BCS and BFT had also higher concentrations of circulating NEFA during the weeks preceding HEC tests, indicating precalving mobilization of body fat (Grummer, 1993;Kokkonen et al, 2005). High levels of circulating NEFA are known to negatively affect the effect of insulin at the level of the glucose and FA metabolism, as demonstrated experimentally in dairy cows by intravenous infusion of tallow emulsion (Pires et al, 2007;Salin et al, 2012) and by prolonged fasting (Oikawa and Oetzel, 2006), whereas in early lactation NEFA level is negatively associated with glucose decrease after insulin injection (Kerestes et al, 2009). Similarly, in the present research, impaired insulin action at the level of the glucose metabolism (EC50 glucose and max glucose ) and the FA metabolism (min NEFA ) was associated with high levels of NEFA in the weeks preceding the HEC test.…”
mentioning
confidence: 57%
“…The protocol of blood sampling and methods of analyzing blood BHBA and glucagon has been described in Selim et al (2014). Plasma insulin, NEFA, and glucose were measured using the methods described by Salin et al (2012). Intra-and interassay coefficients of variation (CV) for glucose measurement were 1.93 and 1.93%, respectively.…”
Section: Body and Blood Measurementsmentioning
confidence: 99%
“…Samples of each concentrate (cereal concentrate, rapeseed meal, and protein supplement) were pooled to form a 2-mo sample for chemical analyses. Contents of DM, OM, CP, and NDF in the feeds and in vitro OM digestibility of forages were determined using methods described by Salin et al (2012). The ME contents of forages were calculated based on the concentration of digestible OM in feed DM (D-3 value; LUKE, 2015).…”
Section: Animals Diets and Experimental Designmentioning
confidence: 99%
“…On the other word, more insulin responsiveness of LS-fed cows may partially attributed to improved energy balance and lower body fat mobilization (Pires et al, 2008). In addition, it has been reported that abomasal infusion of n-3 FA sources such as camelina and linseed oil were effective in altering insulin responsiveness and consequently decrease the level of plasma NEFA (Pires et al, 2008;Salin et al, 2012). To the best of our knowledge, no experiments have been published examining the roles that extruded oil seeds such as linseed and soybean, as the most available sources of n-3 and n-6 FA in ruminant feeding, respectively, play during the transition period in dairy cows.…”
Section: Discussionmentioning
confidence: 97%